Intraocular Lens Power Formulas, Biometry, and Intraoperative Aberrometry: A Review - Kane, Jack X; Chang, David F (Ophthalmology (Rochester, Minn.), 2021)
The refractive outcome of cataract surgery is influenced by the choice of intraocular lens (IOL) power formula and the accuracy of the various devices used to measure the eye (including intraoperative aberrometry [IA]). This review aimed to cover the breadth of literature over the previous 10 years, focusing on 3 main questions: (1) What IOL power formulas currently are available and which is the most accurate? (2) What biometry devices are available, do the measurements they obtain differ from one another, and will this cause a clinically significant change in IOL power selection? and (3) Does IA improve refractive outcomes? A literature review was performed by searching the PubMed database for articles on each of these topics that identified 1313 articles, of which 166 were included in the review. For IOL power formulas, the Kane formula was the most accurate formula over the entire axial length (AL) spectrum and in both the short eye (AL, ≤22.0 mm) and long eye (AL, ≥26.0 mm) subgroups. Other formulas that performed well in the short-eye subgroup were the Olsen (4-factor), Haigis, and Hill-radial basis function (RBF) 1.0. In the long-eye group, the other formulas that performed well included the Barrett Universal II (BUII), Olsen (4-factor), or Holladay 1 with Wang-Koch adjustment. All biometry devices delivered highly reproducible measurements, and most comparative studies showed little difference in the average measures for all the biometric variables between devices. The differences seen resulted in minimal clinically significant effects on IOL power selection. The main difference found between devices was the ability to measure successfully through dense cataracts, with swept-source OCT-based machines performing better than partial coherence interferometry and optical low-coherence reflectometry devices. Intraoperative aberrometry generally improved outcomes for spherical and toric IOLs in eyes both with and without prior refractive surgery when the BUII and Hill-RBF, Barrett toric calculator, or Barrett True-K formulas were not used. When they were used, IA did not result in better outcomes.The refractive outcome of cataract surgery is influenced by the choice of intraocular lens (IOL) power formula and the accuracy of the various devices used to measure the eye (including intraoperative aberrometry [IA]). This review aimed to cover the breadth of literature over the previous 10 years, focusing on 3 main questions: (1) What IOL power formulas currently are available and which is the most accurate? (2) What biometry devices are available, do the measurements they obtain differ from one another, and will this cause a clinically significant change in IOL power selection? and (3) Does IA improve refractive outcomes? A literature review was performed by searching the PubMed database for articles on each of these topics that identified 1313 articles, of which 166 were included in the review. For IOL power formulas, the Kane formula was the most accurate formula over the entire axial length (AL) spectrum and in both the short eye (AL, ≤22.0 mm) and long eye (AL, ≥26.0 mm) subgroups. Other formulas that performed well in the short-eye subgroup were the Olsen (4-factor), Haigis, and Hill-radial basis function (RBF) 1.0. In the long-eye group, the other formulas that performed well included the Barrett Universal II (BUII), Olsen (4-factor), or Holladay 1 with Wang-Koch adjustment. All biometry devices delivered highly reproducible measurements, and most comparative studies showed little difference in the average measures for all the biometric variables between devices. The differences seen resulted in minimal clinically significant effects on IOL power selection. The main difference found between devices was the ability to measure successfully through dense cataracts, with swept-source OCT-based machines performing better than partial coherence interferometry and optical low-coherence reflectometry devices. Intraoperative aberrometry generally improved outcomes for spherical and toric IOLs in eyes both with and without prior refractive surgery when the BUII and Hill-RBF, Barrett toric calculator, or Barrett True-K formulas were not used. When they were used, IA did not result in better outcomes.